Neuron – Digital console innovative by Arup. Issue 3 (November 2020) - Chan, Felix; Lam, Tony
Abstract: At the age of digital era, supervised / unsupervised machine learning, sharp data analysis and neuron network are some of many ways to formulate optimization problems with millions or billions of variables. Classical building system and environmental optimization algorithms are not designed to scale to instances of this size; new approaches are needed. The Digital Platform developed by Arup – Neuron is an innovative console which embodies 5G, IoT, Big Data, Cloud Computing and AI technology for smart building with advanced data analytic capabilities. It can fully integrate with the existing Building Management System as well as various data sources generated from the IoT sensors, enabling prompt and adaptive response to dynamic environment, serving as a foundation for buildings to consolidate and connect data from disparate equipment and devices to provide customised insight and machine learning models for built environmental management and improvement, new building design, operation and asset management, energy monitoring and optimisation. One significant success achieved with our integrated digital platform is that it has been adopted by multiple clients in the East Asia region in managing their building. With full implementation and other appropriate energy saving and/or retro-commissioning practices, Neuron is expected to save up to 30% total HVAC energy consumption for a typical existing commercial building. Apart from energy saving, Neuron also focuses on creating a better indoor environment, which could significantly improve employees' productivity. Neuron, as a smart building console, is set to have a momentous impact on Hong Kong, not only for a better built environment, but also a game changer for the East Asia region to excel in the era of digital economy. This paper elaborates how Neuron could help in digital transformation of new and existing buildings in the new era. The challenges and experiences of projects will also be discussed.Start your abstract here…